Meningkatkan Hasil Belajar dan Motivasi Belajar Matematika Selama Pandemi Covid-19 melalui Penggunaan Aplikasi Google Classroom pada Siswa Kelas VIII-3 SMP Negeri 1 Sei Bingai Tahun Pelajaran 2022-2021 - Lamsah Saragih (Keguruan, 2022)
This study aimed to improve the learning outcomes on Mathematics subjects and learning motivation in class VIII-3 of SMP Negeri 1 Sei Bingai in 2020-2021 academic year through the using of Google Classroom application during the Covid-19 Pandemic for "Relations and Functions" material. The results of data analysis showed an increasing in learning outcomes and student motivation. The initial cycle stage showed the number of students who have completed the KKM (75) as 29% of students. Although they do learning from home, the learning outcomes increased in the first cycle, there were 18 students (65%) had completed the KKM (75). After the second cycle, it increased to 82% of students who had completed the KKM (75). In cycle I, as 21% of students in the "very high" category of learning motivation, as 43% in the "high" category, then as 25% of students in the "less" category and 11% of students in the "very low" category. Then in cycle II, the results of the analysis of students' learning motivation increased with details; as 32% of students in the category of "very high" learning motivation; as 50% of students in the category of "high"; as 18% of students in the category of "less" learning motivation.